Efficacy of a Mediterranean diet supplemented with fatty fish in ameliorating inflammation in paediatric asthma: a randomised controlled trial. Issue 2 (30th October 2018) - Papamichael, M. M.; Katsardis, Ch.; Lambert, K.; Tsoukalas, D.; Koutsilieris, M.; Erbas, B.; Itsiopoulos, C.
Abstract: Background: Childhood asthma is the most common respiratory disorder worldwide, being associated with increased morbidity and a decreased quality of life. Omega‐3 fatty acids have anti‐inflammatory and immunomodulating properties; however, their efficacy in asthma is controversial. The present study aimed to examine the efficacy of a Mediterranean diet supplemented with a high omega‐3 'fatty' fish intake in Greek asthmatic children. Methods: A single‐centred, 6‐month, parallel randomised controlled trial compared the consumption of a Mediterranean diet supplemented with two meals of 150 g of cooked fatty fish weekly (intervention) with the usual diet (control) with respect to pulmonary function in children (aged 5–12 years) with mild asthma. Pulmonary function was assessed using spirometry and bronchial inflammation by fractional exhaled nitric oxide analysis. Results: Sixty‐four children (52% male, 48% female) successfully completed the trial. Fatty fish intake increased in the intervention group from 17 g day −1 at baseline to 46 g day −1 at 6 months ( P  <   0.001). In the unadjusted analysis, the effect of the intervention was of borderline significance ( P  =   0.06, β = −11.93; 95% confidence interval = −24.32 to 0.46). However, after adjusting for age, sex, body mass index and regular physical activity, a significant effect was observed ( P  =   0.04, β = −14.15 ppb; 95% confidence interval = −27.39 to −0.91). No difference was observed for spirometry, asthma control and quality of life scores. Conclusions: A Mediterranean diet supplemented with two fatty fish meals per week might be a potential strategy for reducing airway inflammation in childhood asthma. Future robust clinical trials are warranted to replicate and corroborate these findings.